Health knowledge of prostitutes in Saigon, Vietnam: a study of health attitudes and habits relating to venereal diseases taken from a group of prostitutes - Ruth Sandoval Marcondes; Scott W. Edmonds (Universidade de São Paulo, 1967)
A study of health knowledge and practices of prostitutes is presented here. The study took place at the V. D. Center in Saigon, Vietnam. It was designed with the objective of obtaining information to be used in preparing an educational program to be offered to the prostitutes at the Center, and for using, in preparing educational materials with focus on V. D. prevention. The outline of a course is also presented. Um estudo sôbre conhecimento e práticas de prostitutas em relação a doenças venéreas é objeto dêste trabalho. O estudo foi realizado no Centro de Contrôle de Doenças Venéreas de Saigon, Vietnam com o fim de obter informações que pudessem orientar o planejamento de um programa educativo a ser desenvolvido no Centro e o preparo de recursos audiovisuais, focalizando particularmente a prevenção das doenças venéreas. O esquema de um curso a ser oferecido às internadas é apresentado.